Hydrogen storage properties of magnesium borohydride infiltrated in silica aerogel using solvated and pressure methods. (October 2020) - Rueda, Miriam; Benito-Román, Óscar; Girella, Alessandro; Cofrancesco, Pacifico; Milanese, Chiara
Highlights: α-Mg(BH4 )2 form was infiltrated in microparticles of silica aerogel by wet impregnation and dried using SCCO2 . Wet impregnation infiltration reduced the onset decomposition temperature of the composite by more than 180 °C. The reduction of the particle size and the presence of silica as additive improved the kinetics of all the composites. First time that α-Mg(BH4 )2 is 6.1 wt% H2 reversible at moderate conditions of pressure and temperature. The infiltration method determined the morphology of the composite. Abstract: In this work, the polymorphic α-magnesium borohydride form was infiltrated by wet impregnation using tetrahydrofuran (THF) as solvent and subcritical carbon dioxide as innovative drying process. Pressure infiltration at high temperature was also tested as another promising method for confinement. After infiltration, onset decomposition temperature was reduced from 280 °C into 220 °C using high pressure infiltration and down to 100 °C using wet impregnation followed by CO2 drying. Faster kinetics were obtained in both cases due the possible particle size reduction in the precipitation process of the complex hydride and the presence of silica, which could behave as an additive. It is the first time that this complex borohydride is 6.1 wt% H2 reversible performing the rehydrogenation at moderate conditions of 390 °C and 120 bar H2 using silica as support. Different values were obtained after infiltration method due to the different intermediates that were obtained after the first dehydrogenation. Graphical abstract: Image, graphical abstract